2015
DOI: 10.1108/jmp-06-2013-0187
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative meta-analysis of trust in supervisor-subordinate relationships

Abstract: 71e98a45-9ed4-4c0c-b184-71fb6b5d8bd3/1/. Emerald does not grant permission for this article to be further copied/distributed or hosted elsewhere without the express permission from Emerald Group Publishing Limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 97 publications
3
73
1
1
Order By: Relevance
“…Similarly, the examination of Hypothesis H1b points to the fact that recognition of competences affects trust in managers. This corresponds with the literature on trust antecedents [21]. Further analysis indicates that perception of abilities is an important factor that is related to trust.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, the examination of Hypothesis H1b points to the fact that recognition of competences affects trust in managers. This corresponds with the literature on trust antecedents [21]. Further analysis indicates that perception of abilities is an important factor that is related to trust.…”
Section: Discussionsupporting
confidence: 88%
“…Unstructured and inductive analysis is appropriate to qualitative data and interpretive methodology (Prasad, 2002). The utility of QMA to accomplish this is reflected in its application to extensive study disciplines, including organisational studies (Berte et al, 2010); property studies (Maginn et al, 2015), managerial psychology (Nienaber et al, 2015) and construction innovation (Hosseini et al, 2015). The ontological disposition of this methodology recognises Gruber's (1993) and Studer et al's (1998) view that the subject of PMH&S is an "[…] explicit specification of a concept […]" whose entities coexist to characterise that concept, such that "[…] relationships hold among them" (Gruber, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…While it has been on the radar for several decades, more recent research focuses on the in‐depth components of transformational leadership, specifically: Trust—Trust between leader and follower is critical in building a culture of empowerment, equality, and respect. Recent research has found that transformational leadership can build the needed trust between leader and follower that is often eroded within complex organizational cultures (Nienaber, Romeike, Searle, & Schewe, ). Emotional Intelligence—The influence and necessity for emotional intelligence and emotional regulation are discussed in several articles, particularly in regard to trait‐based measures associated with transformational leadership (Kim & Kim, ). Relationship to Other Leadership Styles—Transformational leadership correlates well with newer leadership styles of servant, authentic, and ethical leadership, emphasizing integrity and the high moral component associated with each (Hock, Bommer, Dulebohn, & Wu, ). …”
Section: Emerging Ideas About Transformational Leadershipmentioning
confidence: 99%